2018
DOI: 10.1177/0020731418779377
|View full text |Cite
|
Sign up to set email alerts
|

How Single-payer Stacks Up: Evaluating Different Models of Universal Health Coverage on Cost, Access, and Quality

Abstract: Described as "universal prepayment," the national health insurance (or single-payer) model of universal health coverage is increasingly promoted by international actors as a means of raising revenue for health care and improving social risk protection in low- and middle-income countries. Likewise, in the United States, the recent failed efforts to repeal and replace the Affordable Care Act have renewed debate about where to go next with health reform and arguably opened the door for a single-payer, Medicare-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Universal health care would address the current insurance coverage disparities faced by racial and ethnic minorities, who are more likely to face unemployment and underinsurance due to the pandemic 94,97 . Despite the potential that universal health care—whether through a socialized single‐payer system as in the United Kingdom, social insurance as in Germany, or a mixed public and private model as in the Netherlands 98 —offers to mitigate economic and accessibility barriers to health care, 98 it is currently contested in the United States 99 …”
Section: Addressing the Social Determinants Of Health In The United Statesmentioning
confidence: 99%
“…Universal health care would address the current insurance coverage disparities faced by racial and ethnic minorities, who are more likely to face unemployment and underinsurance due to the pandemic 94,97 . Despite the potential that universal health care—whether through a socialized single‐payer system as in the United Kingdom, social insurance as in Germany, or a mixed public and private model as in the Netherlands 98 —offers to mitigate economic and accessibility barriers to health care, 98 it is currently contested in the United States 99 …”
Section: Addressing the Social Determinants Of Health In The United Statesmentioning
confidence: 99%
“…Additionally, loss of choice and increased wait times are further caricatures of single-payer that are easily exploited to dampen support, even though crossnational comparisons do not bear this out. 35 Thus, the strategy of the opposition is to paint the reform team as unrealistic and fiscally irresponsible.…”
Section: Interest Group Politicsmentioning
confidence: 99%
“…32 In fact, comparative studies drawing on research from the Commonwealth Fund's National Health Systems Study have found no inherent tendency of singlepayer systems to have longer wait times or higher dissatisfaction than the US. 35 Though for the majority of beneficiaries, the amount they pay in payroll taxes is estimated to be less than the amount they currently pay in premiums, for some beneficiaries, they may end up paying more either because they were not paying anything before or if they fall in the highest income brackets due to the progressive tax financing proposed.…”
Section: Beneficiary Politicsmentioning
confidence: 99%
“…[14] Given the performance of single-payer models showing consistently stronger results across multiple dimensions of healthcare, it is a viable reform option for the U.S. to explore. [15] The COVID-19 pandemic that began in early 2020 has had a deleterious effect on healthcare, notwithstanding a tremendous financial impact on healthcare systems. [16] The pandemic's full impact remains unknown, however the traditional fee for service and payment models come under additional stress and scrutiny as a result.…”
Section: Introductionmentioning
confidence: 99%